Experiencing Dracula's homeland. Issue 5 (20th October 2017) - Lupu, Cristina; Brochado, Ana; Stoleriu, Oana Mihaela
ABSTRACT: Transylvania has not only a geographical location as a province of Romania but also a mental meaning as Dracula's land. Dracula has become an important brand name for Romania, attracting many tourists in recent years – especially after the fall of communism. The main dimensions of Dracula's castle (i.e. Bran Castle) experiences shared online by tourists were identified to ascertain the primary reasons for satisfaction and dissatisfaction with visits and to test whether narratives and satisfaction vary according to the occasion (i.e. Halloween). Quantitative (i.e. computer-based) and qualitative (i.e. narrative) content analyses were conducted on the Web reviews written by visitors. The results reveal that the experiences are multidimensional, and they include the following themes: 'castle', 'visit', 'Dracula', 'inside', 'tourist', 'outside', 'trip', 'souvenirs', 'stairs' and 'Dracula's castle'. The main reasons for dissatisfaction are overcrowding, which is connected with the outside theme, and the disappointment of tourists regarding the old furniture, which is associated with the inside theme. The results also reveal that visitors are the most satisfied with their experience around the time of Halloween. The narratives shared online emphasise tourists' need to associate their imaginings with this region and castle, giving their experiences greater meaning through this destination's image as Transylvania.